Correlation between dietary intake and serum ganglioside concentrations: a cross-sectional study among Malaysian toddlers - Geok, Lin Khor; Shyam, Sangeetha; Misra, Snigdha; Fong, Bertram; Hueh, Megan Zan Chong; Sulaiman, Norhasmah; Yee, Lin Lee; Cannan, Rabecca; Rowan, Angela (BioMed Central, 2016)
Background: Gangliosides are a group of sialylglycosphingolipids, widely distributed in body tissues, mainly as components of plasma membranes. They play crucial roles in neurodevelopment, gut maturation, and immune system. Dietary gangliosides have been shown to bring about benefits including cognition and immune support for breastfed infants. There is dearth of studies on dietary gangliosides intake or plasma ganglioside levels for toddlers. Given toddlers are still growing rapidly, a good understanding of ganglioside intake during this early childhood period is important for future dietary recommendations. The aim of this study was to provide information on dietary ganglioside intake in Malaysian toddlers and correlations with serum ganglioside levels. Methods: Toddlers who fulfilled the inclusion criteria were recruited from the Federal Territory of Putrajaya and neighboring urban suburbs. Background characteristics and food intake using food frequency questionnaire were collected for the entire sample (n = 153). As for ganglioside correlation determination, a 2 day weighed food record was conducted on a sub-group who provided blood (n = 74). Ganglioside levels in the food and blood were determined using modern high performance liquid chromatography mass spectrometry method. Results: The average dietary intake of total gangliosides for the Malaysian toddlers (aged 12–24.5 months) was 5.86 ± 0.56 mg/day. Growing up milks had a wide ganglioside concentration range (0.03 11.4 mg/100 g), and were the major contributor to dietary ganglioside intake (85%). The remaining dietary gangliosides were provided by other dairy products, meat, fish, bakery and biscuits.Serum levels varied from 5.05 μg/mL to 16.15 μg/mL. While no significant correlation was observed between dietary ganglioside intake from growing up milks and serum ganglioside levels in the toddlers, there was a significant but weak correlation between dietary ganglioside intake from dairy products (r = 0.241; p = 0.038) and meat (r = 0.294; p = 0.010) with serum ganglioside levels. Conclusions: Gangliosides are a component of the Malaysian toddlers’ diet (5.68 ± 0.56 mg/day), and were measured in their plasma at levels ranging from 5.05 to 16.15 μg/mL. Growing up milk contributed to 85% of the total dietary gangliosides intake, with remaining contributions from chicken meat and fish. More studies should be undertaken on the contributions of dietary gangliosides, including breast milk, in bringing about health benefits to young children.